Real-time emission characterization of organic air toxic pollutants during steady state and transient operation of a medium duty diesel engine - Gullett, Brian K.; Touati, Abderrahmane; Oudejans, Lukas; Ryan, Shawn P. (Atmospheric environment (1994), 2006)
An on-line monitoring method, jet resonance-enhanced multi-photon ionization (REMPI) with time-of-flight mass spectrometry (TOFMS), was used to measure emissions of organic air toxics from a medium-duty (60 kW) diesel generator during transient and steady state operations. Emissions of gas phase benzene, toluene, ethylbenzene, o-, m-, p-xylenes (BTEX), styrene and polycyclic aromatic hydrocarbons (PAHs) were measured at levels in the 10–500 ppb range with a measurement frequency of 10 s −1; this enabled rapid emission characterization as a function of operating conditions: cold starts, hot starts and load changes. The sensitivity, selectivity and real-time monitoring capabilities of the jet REMPI-TOFMS system discerned transient concentrations of organic air toxics (e.g., benzene and naphthalene) during cold starts exceeding 15 times their steady state levels. Time-integrated concentrations obtained by jet REMPI-TOFMS compared well with standard EPA methods. The jet REMPI-TOFMS system provides a means to rapidly characterize air toxic emission factors that enables users to alter operational procedures to minimize air toxic formation. The relative concentrations between startup and steady state emissions, as well as the transition period between these levels, were specific for each type of compound found in the diesel exhaust.